Odpowiedź :
- 7x - 9 + 10 - 5= 3x - 14
5k - 4 + 9-k= 4k + 5
4 - 3y - 10 + 7y = -6 +4y
-8d + 1 + d -9 = -7d -8
6w - 3 - 8 + 5w = 11w - 11
4z - 6 + 1 - 9z = -5z - 5
4x
-5w - 7
-3y - 11
-9y
Odpowiedź:
zad 1
a) – (7x +9) – (– 10x +5) =3x-14
b) (5k – 4) + (9 – k) =4k+5
c) (4 – 3y) – (10 – 7y) =4y-6
d) (–8d +1) + (d – 9) =-7d-8
e) –(–6w + 3) – (8 – 5w) =11w-11
f) (4z – 6) + (1 – 9z) =-5z-5
zad 2
a) 5x – x =4x
b) 7w + 3 – 12w – 10 =-5w-7
c) 8y – 9 +3 – 12y + y – 5 =-3y-11
d) –10 y + y=-9y
Szczegółowe wyjaśnienie: